Criminal Law Formulation Policy Regarding Payment of Money In Substitution For Criminal Acts of Corruption From The Perspective of Dignified Justice - Ni'Am, M. Khoirun; Prija Djatmika; Abdul Madjid (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
Corruption is an extraordinary crime that remains a serious problem in Indonesia despite the implementation of various regulations such as Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption. One important instrument in recovering state losses due to corruption is the penalty of replacement money. However, in practice, the application of replacement money as an additional penalty has not been effective due to legal and technical obstacles, such as the difficulty of tracking assets, weak coordination between law enforcement agencies, and the absence of a consistent execution mechanism. This study aims to analyze the legal implications of criminal law formulation policies related to the regulation of replacement money and to formulate a direction for criminal law reform based on the concept of dignified justice. This study uses a normative legal research method with a statutory, case, and conceptual approach. The analysis is conducted prescriptively through grammatical and systematic interpretation of laws and regulations, doctrine, and judicial practice. The results show that the regulation of replacement money as an additional penalty does not reflect substantive justice because it emphasizes the retributive aspect rather than the restorative aspect. Legal reform is needed by making compensation a primary punishment so that the primary objective of punishment is to restore state losses. The dignified justice approach positions humans as moral subjects responsible for redressing public losses, in line with the values ​​of Pancasila. Therefore, this reformulation is expected to create a more just, humane, and socially just criminal legal system.